Probiotic Supplementation During Human Pregnancy Affects the Gut Microbiota and Immune Status - Chen, Yuyi; Li, Zhe; Tye, Kian Deng; Luo, Huijuan; Tang, Xiaomei; Liao, Yu; Wang, Dongju; Zhou, Juan; Yang, Ping; Li, Yimi; Su, Yingbing; Xiao, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2019)
The consumption of probiotics and fermented foods has been very popular in recent decades. The primary aim of our study was to evaluate the effect of probiotics on the gut microbiota and the changes in inflammatory cytokines after an average of 6.7 weeks of probiotic administration in normal pregnant women. Thirty-two healthy pregnant women at 32 weeks of gestation were recruited and divided into two groups. The probiotics group ingested combined probiotics until antepartum. The base characteristics of the probiotics and control groups showed no significant differences. The structure of the fecal microbiota at the genus level varies during the third trimester, and administration of probiotics had no influence on that; however, many highly abundant taxa and core microbiota at the genus level changed in the probiotics group compared to the control group. The analysis of cytokines showed that IL-5, IL-6, TNF-α and GM-CSF, had equal levels between the baseline and control groups but significantly increased after probiotic administration (baseline = control < probiotics). Additionally, IL-1β, IL-2, IL-12 and IFN-γ increased significantly among the three groups (baseline < control < probiotics). It demonstrated that probiotics helped to shift the Anti-inflammatory state to a pro-inflammatory state. The correlation analysis outcome suggested that the relationship between the microbiota and the cytokines was not strain-dependent. The gut microbiota varied during the third trimester. The probiotics had immunomodulation effects that helped to switch to pro-inflammatory immune state in the third trimester which was important to labour.